Mergers and Acquisitions in Russian Oil Industry - Borovskaya, Nataliya (2005)
Mergers and acquisitions are not a recent phenomena and its growing activity over years can be explained by companies desire to achieve corporate diversity and growth and renew market position at a speed which could not be achievable through the internal development. The increasing number of M&A activity not only domestically, but also on an international scale, became possible due to globalization, liberalization of markets, declining trade barriers, diversification of many industries and technological improvement.